Optimalisasi Kinerja Sumber Daya Manusia Melalui Perbaikan Struktur Organisasi, Job Desk dan Rantai Komando pada Usaha: Vendor UNAIR - Dicky Zafirin Qodriansyah; Tiffany Maureen Loudya Auva; Athirah Zafirah; Hafiz Aulia Dianto; Muhammad Haikal Najmu Tsakib; Abdu Alrozak Alfa Virera; Buhayyah Putri Ayu Pertiwi; Tri Siwi Agustina; Jhon Hardi (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Campus based microenterprises have significant growth potential but often encounter structural challenges, particularly in human resource management. This study aims to optimize the performance of human resources at Vendor Unair a student-oriented microenterprise that produces organizational merchandise through improvements in organizational structure, job descriptions, and chain of command. A descriptive qualitative method was used with a participatory approach, involving observation, informal interviews, and role simulations. Findings indicate that the business initially operated without a formal organizational structure, with task assignments handled spontaneously. After the mentoring process, a three-level organizational structure was implemented along with ten clearly defined job descriptions. These changes improved team coordination and operational efficiency. The study concludes that a participatory approach can serve as an effective managerial solution for non-formal microenterprises.